Laboratory and field study of fatigue cracking prediction in asphalt pavements. - Bessa, Iuri Sidney (2017)
The prediction of asphalt pavements performance in relation to their main distresses has been proposed by different researchers, by means of laboratory characterization and field data evaluation. In relation to fatigue cracking, there is no universal consensus about the laboratory testing to be performed, the damage criterion to be considered, the testing condition to be set (level and frequency of loading, and temperature), and the specimen geometry to be used. Tests performed in asphalt binders and in asphalt mixes are used to study fatigue behavior and to predict fatigue life. The characterization of asphalt binders is relevant, since fatigue cracking is highly dependent on the rheological characteristics of these materials. In the present research, the linear viscoelastic characterization, time sweep tests, and amplitude sweep tests were done. In respect to the laboratorial characterization of asphalt mixes, tests based on indirect tensile, four point flexural bending beam, and tension-compression were performed. Field damage evolution data of two asphalt pavement sections were collected from an experimental test site in a very heavy traffic highway. Three asphalt binders (one neat binder, one SBS-modified binder and one highly modified binder, HiMA), and one asphalt concrete constituted by the neat binder were tested in laboratory. The experimental test site was composed by two segments, constituted by different base layers (unbound course and cement-treated crushed stone) that provided different mechanical responses in the asphalt wearing course. The field damage data were compared to fatigue life models that use empirical results obtained in the laboratory and computer simulations. Correlations among the asphalt materials scales were discussed in this dissertation, with the objective of predicting the fatigue cracking performance of asphalt pavements.